2014
DOI: 10.1111/bjh.13255
|View full text |Cite
|
Sign up to set email alerts
|

Superficial vein thrombosis: a current approach to management

Abstract: SummarySuperficial vein thrombosis (SVT) was considered to be a benign and self-limiting condition. However, it is now appreciated that a significant proportion of those presenting with SVT will have concomitant deep vein thrombosis or pulmonary embolism, or are at significant risk of developing deep venous thromboembolism. Potential therapeutic options include topical preparations, compression therapy (stockings, bandages), medication such as non-steroidal anti-inflammatory drugs (NSAIDs) or anticoagulants (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 43 publications
0
26
0
8
Order By: Relevance
“…11 Finally, prophylactic dose anticoagulation has been shown to be effective in the treatment of SVT. 9 In conclusion, KTWS is a rare condition that can be complicated by a variety of thrombotic manifestations. Recurrent overt thrombotic events may be successfully treated with anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Finally, prophylactic dose anticoagulation has been shown to be effective in the treatment of SVT. 9 In conclusion, KTWS is a rare condition that can be complicated by a variety of thrombotic manifestations. Recurrent overt thrombotic events may be successfully treated with anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is data to support the use of short term low dose anticoagulation in the treatment of acute superficial vein thrombosis (SVT). 9 Randomized controlled studies have demonstrated the efficacy and safety of systemic anticoagulation with therapeutic/intermediate doses of LMWH or prophylactic doses of fondaparinux administered for 4-6 weeks. 9 Fondaparinux 2.5 mg/day is currently the only anticoagulant with a license for the treatment of SVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant number (25%) of patients with SVT shows gradual extension in the vein to manifest as DVT and PE. 127,128 When SVT of the lower limbs extends .5 cm in length, it should be treated for 45 days with prophylactic doses of FON or LMWH in combination with anti-inflammatory agents. 129 Provoked SVT typically occurs in upper extremities (cephalic and basilic veins), following the placement of IV lines (peripheral IV catheters or PICC).…”
Section: Management Of Thrombosis In Unusual Locationsmentioning
confidence: 99%
“…Ayrıca, variköz venlerde gelişen YVT ilerleyerek derin ven sistemine geçebileceğinden özellikle tromboze variköz venleri olan hastaların sıkı takibi gerekir. Safenofemoral kavşağa 3 cm'den daha yakın yüzeyel ven trombozlarında olası komplikasyonları önlemek için antikoagülan tedavi ve cerrahi ligasyon veya trombektomi uygulanmalıdır (15). FVL mutasyonu beyaz ırkta en yaygın rastlanan kalıtsal trombofili nedenidir.…”
Section: Introductionunclassified